A construção da identidade no conto fonsequiano: a intertextualidade e a morte como afirmação do estrangeiro - FERREIRA, João Paulo Cordeiro (Universidade Federal do Pará, 2019)
In Rubem Fonseca's tales, it is common to find several "intertextualized" discourses, with works, characters, quotations and discussions around famous Brazilian and foreign literary authors who are, in different contexts and literary constructions, placed in the fonsequiana prose, directly or indirectly. In this way, we will take an approach taking into account three important short stories of Fonseca: "Encontro no Amazonas" (from the book O Cobrador), "Romance Negro" (from Romance Negro) and "A matéria do sonho" (from the book Lúcia McCartney). The reading of these tales, in part, suggests to us that there is an intense dialogue between the national and the foreigner, in which death assumes a decisive role for the self-assertion of the foreign tradition in our literature. This dialogue also allows us to identify the relationship between the fonsequiana prose and the narratives of E.T.A. Hoffmann and Edgar A. Poe, since it is possible that some compositions of these authors have drawn a dialogue with the literary constructions of Rubem Fonseca, which in this sense made possible the re- reading of the works of Poe and Hoffmann. In this way, we also emphasize the relation of the fonsequiana prose with the Greek tragedy, relating the use of the mask to the farce and the exchange of identity in the Rubem Fonseca literature. To this end, we consider Maurice Blanchot's theories about the death of the author, Otto Rank, referring to the notion of double and Sigmund Freud, about psychoanalysis.